Creating a successful wildlife education program for public schools - Sykes, Debbie (Wildlife Rehabilitation Bulletin, 2022)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">There are many ways to organize and execute a wildlife education program. While there are numerous resources for wildlife rehabilitators on public education, there are few that include school-aged children. A successful approach to wildlife education in the public school classroom takes into consideration developmental characteristics for preschool through high school students, teaching styles, and matches programs with state standards. English language learners and students of schools in lower income areas require special considerations.